2016
DOI: 10.1080/17515831.2016.1262587
|View full text |Cite
|
Sign up to set email alerts
|

Effect of bimodal size particles reinforcement on the wear, friction and mechanical properties of brake composites

Abstract: Novel bimodal size ranges of ceramic particles (SiC (115 μm)and SiO 2 (1.2 μm) (labelled as SIL)), SiC (115 μm) and mullite (4 μm) (labelled as MUL)) iron matrix composite structures were processed by powder metallurgy. The physical, mechanical and tribological properties were evaluated for these composites. The dry sliding wear and friction tests were conducted at ambient temperature and 60% humidity in a laboratory scale dynamometer for braking material applications. We have selected four braking speeds (5,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 30 publications
2
8
0
Order By: Relevance
“…With respect to normal pressure, there are not significant changes in μ when pressure increases. This behavior has also been found in other studies [18, 23].…”
Section: Resultssupporting
confidence: 90%
“…With respect to normal pressure, there are not significant changes in μ when pressure increases. This behavior has also been found in other studies [18, 23].…”
Section: Resultssupporting
confidence: 90%
“…The authors showed that a ratio of 3:1 (between the smaller size particles and bigger particles) resulted in the maximum nano-hardness and minimum wear rates. Prabhu [ 101 ] processed Fe-based composites where the Fe matrix was reinforced with bimodal-size dissimilar nature (SiC and SiO 2 ) particles through powder metallurgy. The author showed that the addition of bimodal-size particles improves the wear resistance of the composites significantly by comparison with single-size-particle reinforced composites.…”
Section: Mechanical and Tribological Properties Of Al-based Mmcsmentioning
confidence: 99%
“…The maximum wear rate is observed in the un-heat treated Al2014 matrix alloy. The possible reason for this is extensive subsurface deformation, high adhesive metal-metal contact that assisted surface shear strain, and the absence of load-bearing particles [55][56][57]. The difference in wear rate of the Al2014 matrix alloy and Al2014-15 wt.% Al 2 O 3 composites before and after heat-treated conditions with variable loads is shown in Figure 8.…”
Section: Fatigue Testmentioning
confidence: 99%
“…The maximum wear rate is observed in the un-heat treated Al2014 matrix alloy. The possible reason for this is extensive subsurface deformation, high adhesive metal-metal contact that assisted surface shear strain, and the absence of load-bearing particles [55][56][57].…”
Section: Fatigue Testmentioning
confidence: 99%